Applications of high-silicon aluminum alloys to dissimilar materials joining - Yang, Yongjing (Nanyang Technological University, 2023)
High-silicon aluminum (high-Si Al) alloys have been utilized in many engineering applications owing to the advantages of low density, good wear resistance and low coefficient of thermal expansion (CTE). Joining of high-Si Al alloys to other materials with dissimilar properties could combine their advantages to expand the applications of high-Si Al alloys. In this work, a simple and convenient approach for dissimilar material joining between ceramics and a wide range of Al alloys was developed through the use of high-Si Al alloys.